Originally Posted by
FlexedCookie Hi all.
I got this question from my example booklet, which has the question worked. However, im not quite sure how the problem is solved, and i cant follow how the exmaple booklet does it.
If someone could break down the steps for me that would be amazing.
This is what the booklets steps are:
-300 = 0 + (1/2) * (-9.8) * t^2
t^2 = -300 * 2 / -9.8
t^2=61.22
hence, t = 7.8s
I dont understand how it goes from the first line to the second one.
Any help would be greatly appreciated.
Thanks.